Reduced-port laparoscopic appendectomy for acute appendicitis in pregnancy. Issue 6 (15th June 2020) - Hata, Tsuyoshi; Hayashi, Nobuyasu; Urabe, Shoichiro; Hayashi, Koji; Nakagawa, Tomo; Michiura, Toshiya; Yamabe, Kazuo
Abstract: Current guidelines indicate that laparoscopic appendectomies are safe for pregnant patients with acute appendicitis. Recently, single- and reduced-port laparoscopic surgeries have gained popularity for nonpregnant patients, because they minimize abdominal wall trauma. Here, we describe a reduced-port laparoscopic appendectomy (RPLA) in a 31-year-old pregnant female performed at 27 weeks gestational age. Preoperative abdominal ultrasonography and computed tomography imaging showed an inflamed, swollen appendix and blood test results showed elevations in the white blood cell count and the C-reactive protein level. Accordingly, acute appendicitis was diagnosed. A surgical incision was performed at the umbilicus with an EZ-access device; an additional 5-mm trocar was placed at the right lower quadrant. Recovery was uneventful. The patient was discharged 8 days postoperatively. A vaginal delivery was achieved at term. The RPLA was a good surgical option for minimizing surgical invasiveness, without increasing the technical difficulty, in conditions where the uterus and fetus are growing.